Genomic evidence of contemporary hybridization between Schistosoma species. - Duncan J Berger; Elsa Léger; Geetha Sankaranarayanan; Mariama Sène; Nicolas D Diouf; Muriel Rabone; Aidan Emery; Fiona Allan; James A Cotton; Matthew Berriman; Joanne P Webster (PLoS Pathogens)
Hybridization between different species of parasites is increasingly being recognised as a major public and veterinary health concern at the interface of infectious diseases biology, evolution, epidemiology and ultimately control. Recent research has revealed that viable hybrids and introgressed lineages between Schistosoma spp. are prevalent across Africa and beyond, including those with zoonotic potential. However, it remains unclear whether these hybrid lineages represent recent hybridization events, suggesting hybridization is ongoing, and/or whether they represent introgressed lineages derived from ancient hybridization events. In human schistosomiasis, investigation is hampered by the inaccessibility of adult-stage worms due to their intravascular location, an issue which can be circumvented by post-mortem of livestock at abattoirs for Schistosoma spp. of known zoonotic potential. To characterise the composition of naturally-occurring schistosome hybrids, we performed whole-genome sequencing of 21 natural livestock infective schistosome isolates. To facilitate this, we also assembled a de novo chromosomal-scale draft assembly of Schistosoma curassoni. Genomic analyses identified isolates of S. bovis, S. curassoni and hybrids between the two species, all of which were early generation hybrids with multiple generations found within the same host. These results show that hybridization is an ongoing process within natural populations with the potential to further challenge elimination efforts against schistosomiasis.